Feasibility of a PBL module integrating West Kalimantan’s biodiversity for organism classification in junior high schools - Kurnia Ningsih; Mas Akhbar Faturrahman; A. Afandi; T. Titin (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The integration of local biodiversity into teaching materials based on innovative learning models remains limited, despite its potential to offer a context-rich and meaningful approach to Natural Sciences learning. To address this gap, this research incorporates the biodiversity of West Kalimantan into a problem-based learning (PBL) module on organism classification—a topic considered difficult for junior high school students. Accordingly, this research aims to evaluate the feasibility of the developed module through content validity and interrater reliability, using a Research and Development method consisting of five stages: potential and problems, data collection, product design, design validation, and design revision. The instruments utilized were an interview guideline, an instrument validation sheet, and a product design validation sheet. Six validators then validated the module. Content validity was analyzed using Aiken’s validity index, while interrater reliability was analyzed using the Intraclass Correlation Coefficient (ICC) test. The content validation results showed an average validity index of 0.98, categorized as valid. Interrater reliability using the ICC test yielded a value of 0.751, categorized as good. Therefore, the developed module is feasible for Natural Sciences learning and strengthens the implementation of PBL by contextualizing scientific concepts through the unique biodiversity and authentic issues of West Kalimantan.